Metagenome-assembled genomes provide insight into the metabolic potential during early production of Hydraulic Fracturing Test Site 2 in the Delaware Basin - Stemple, Brooke; Gulliver, Djuna; Sarkar, Preom; Tinker, Kara; Bibby, Kyle (Frontiers in Microbiology, 2024)
Demand for natural gas conKnues to climb in the United States, having reached a record monthly high of 104.9 billion cubic feet per day (Bcf/d) in November of 2023 (1).Hydraulic fracturing, a technique used to extract natural gas and oil from deep underground reservoirs, involves injecKng large volumes of fluid, proppant, and chemical addiKves into shale units. This is followed by a "shut-in" period, during which the fracture fluid remains pressurized in the well for several weeks. The microbial processes that occur within the reservoir during this shut-in period are not well understood; yet, these reacKons may significantly impact the structural integrity and overall recovery of oil and gas from the well. To shed light on this criKcal phase, we conducted an analysis of both pre-shut-in material alongside producKon fluid collected